2016
DOI: 10.12659/msm.897965
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Status in Childhood Obesity: A Potential Risk Predictor

Abstract: BackgroundChildhood obesity characterized by excessive fat in the body is one of the most serious health problems worldwide due to the social, medical, and physiological complications. Obesity and associated diseases are triggering factors for oxidative stress and inflammation. The aim of this study was to explore the possible association between childhood obesity and inflammatory and oxidative status.Material/MethodsThirty-seven obese children and 37 healthy controls selected from among children admitted to B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 37 publications
(36 reference statements)
2
30
0
1
Order By: Relevance
“…Although there are several available definitions of MU status, there is evidence that both childhood obesity and MU status increase cardiovascular disease risk in adulthood [4,5]. Moreover, systemic inflammation and endothelial damage have also been described in children with obesity [6,7], as well as increased oxidative stress [8,9]. The relationship between oxidative stress, obesity, and cardiometabolic disease seems to be a consequence of low-grade inflammation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several available definitions of MU status, there is evidence that both childhood obesity and MU status increase cardiovascular disease risk in adulthood [4,5]. Moreover, systemic inflammation and endothelial damage have also been described in children with obesity [6,7], as well as increased oxidative stress [8,9]. The relationship between oxidative stress, obesity, and cardiometabolic disease seems to be a consequence of low-grade inflammation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some have suggested this may vary according to the degree of the disease development and/or severity [ 8 ]. Nevertheless, most published studies measure these biomarkers in basal conditions [ 9 , 10 ], but their dynamics after a stressor, such as a glucose overload (OGTT), and more specifically, at pediatric age has not been explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…However, Omu, Fatinikun, Mannazhath, and Abraham (1999) reported that α-TOH concentration is higher in blood than in semen and that concentration was higher in samples of (2009) showed an association between low semen α-TOH concentration and altered sperm function in 40 patients with different seminal parameters. However, the authors considered only obese men with an average BMI of about 35, which is known to affect the antioxidant status (Kilic et al, 2016;Ozata et al, 2002). Our patients had a BMI < 30 kg/m 2 and a comparable smoking status.…”
Section: Discussionmentioning
confidence: 99%